A Double Conformationally Restricted Dynamic Supramolecular System for the Substrate‐Selective Epoxidation of Olefins—A Comparative Study on the Influence of Preorganization. Issue 2 (8th December 2014) - Lindbäck, Emil; Cherraben, Sawsen; Francoïa, Jean‐Patrick; Sheibani, Esmaeil; Lukowski, Bartosz; Proñ, Agnieszka; Norouzi‐Arasi, Hassan; Månsson, Kristoffer; Bujalowski, Pawel; Cederbalk, Anna; Pham, Thanh Huong; Wixe, Torbjörn; et al.
Abstract A double conformationally restricted kinetically labile supramolecular catalytic system, the third generation, was designed and synthesized. We investigated the substrate selectivity of this system by performing competitive pairwise epoxidations of pyridyl‐ and phenyl‐appended olefins. We compared the obtained substrate selectivities to previous less preorganized generations of this system. Five different substrate pairs were investigated, and the present double conformationally restricted system showed higher normalized substrate selectivities (pyridyl versus phenyl) for two of the substrate pairs than the previous less conformationally restricted generations. As for the preorganization of the components of the system, the catalyst, and the receptor part, it was shown that for each substrate pair there was one generation that was better than the other to generate substrate‐selective catalysis.